Exploration of Mathematical Patterns in Traditional Cang Kuning Food in Sulawesi - Rahmaniyah, Aulia'ur; Nur, Fitriani; Tayeb, Thamrin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to explore ethnomathematics elements in traditional Cang Kuning food, especially in the concept of geometry and its presentation patterns, and to integrate Cang Kuning as a contextual and relevant mathematics learning medium for students' lives. Methodology: This study uses a qualitative approach with an ethnographic research type. The tools used include interview sheets, observation sheets, and visual documentation. Data collection methods consist of participant observation and in-depth interviews. A literature review was conducted to support the analysis, while the software used for data analysis was NVivo. Main Findings: This study shows that Cang Kuning cake contains various mathematical concepts, including comparison, similarity, and spatial shapes. The process of making the cake reflects the application of geometry in its design and presentation. This cake also has significant cultural value, reflecting the philosophy of the Bugis people and has the potential as a contextual mathematics learning medium. Novelty/Originality of this study: The novelty of this research lies in the exploration of ethnomathematics in traditional Cang Kuning food, which has not been widely studied before. This research develops knowledge about the integration of culture and mathematics, and shows the importance of cultural context in mathematics learning. This provides new insights for educators to create more relevant and interesting learning methods for students.